Participants’ perceptions of the implementation of the MASTEC project, a school improvement project in the Limpopo province of South Africa - Phewa, Molly Cynthia Nombulelo (2010)
The research reported in this thesis was an exploration of the perceptions and lived experiences of participants in the Mathematics, Science and Technology Education College (MASTEC) project, a school improvement project in the Limpopo province of South Africa. The MASTEC project was introduced with the aim of improving provision of both experienced teachers’ in-service training (INSET) and potential teachers’ pre-service training (PRESET). This study sought to examine teacher educators’ and school teachers’ perceptions of issues relating to the implementation of MASTEC in the different contexts of its participant schools.